Bibliometric Analysis of Studies on the Concept of Financial Literacy - Sipahi Döngül, Esra; Skica, Tomasz (Journal of Finance and Financial Law, 2023)
The purpose of the article. This paper attempts to reveal the effect of the study by visually presenting the analysis of the studies on the concept of "financial literacy". Methodology. Bibliometric analysis of the studies published in the Web of Science (WOS) database between 1991 and 2023 was analyzed with the VOSviewer (Version 1.6.9) package program. Since the title, content, and keyword of the concept of "financial literacy" were intended to be scanned in all languages and all publication types, 2,889 works were accessed and analyzed. The limitations of the study are that only the studies in WOS are analyzed. No data from Scopus and PubMed databases has been included. For future studies, research from the Scopus and PubMed databases should be added. Results of the research. When the most frequently included keywords in the publications related to the concept of "financial literacy" have a relationship between them at least twice in the study, the keywords "financial literacy" with 825 repetitions in terms of 1841 total connection strength, "financial education" with 111 repetitions in terms of 315 total connection strength, "financial behavior" with 65 repetitions in terms of 217 total connection strength and "financial knowledge" with 71 repetitions in terms of 213 total connection power are seen. As a result of the analysis performed, it was determined that there were 2265 connection powers and 4069 total connection powers for a total of 36 clusters. When we look at the year-by-year distribution, the most works were published in 2022 with a maximum of 426 works. At least one work was published in 2004, 2003, 1998, 1994 and 1991. Among the published studies, journal article 2,515, proceedings paper 280, early access 135, book chapters 101, review article 68, editorial material 29, correction 6, book 5, book review 3 were determined as works. When we look at the languages in which the published works are published, they are in English with a maximum of 2,814 works. At least two works are in French and Chinese. In order to determine the year-based stratification status of the published studies for country-based citations, it was noted that a country should have at least 1 study published and at least 1 citation obtained. As a result of the analysis, analysis was carried out on 78 observation units that were found to have a relationship between them, and it was determined that there were 14 clusters, 1065 connection power and 9417 total connection power. The countries with the most citations are the USA (11981 citations), the Netherlands (2445 citations) and England (1685 citations). In terms of the number of works, the ranking is the USA (197 publications), China (77 publications), India (73 publications), and Australia (70 publications). When the stratification status of the citation ties of the countries on a yearly basis is examined, it is seen that they are limited between 2017 and 2021.